Composite Lymphoma: Hodgkin and Non-Hodgkin Lymphoma A Case Report - Soetandyo, Noorwati; Rebecca, Ruth Vonky; Yunti, Maria; Reksodiputro, Arry Harryanto (UI Scholars Hub, 2018)
Composite lymphoma (CL) is a rare disease. Composite lymphoma is two or more different type of lymphoma that sequentially or simultaneously occur in one anatomical site. Making a diagnosis of CL is a challenge and there is still no guidelines about the treatment. This case report is about a 36 y.o female with CL, sequentially consisted of Hodgkin and non-Hodgkin lymphoma.